Injection Tests and Effect On Microstructure and Properties of Aluminium 7075 Direct Thermal Method Feedstock Billets - Asnul Hadi, Ahmad; S., Naher; D., Brabazon (Trans Tech Publications, 2014)
The success of semi-solid metal forming is dependent on a globular solid grain formation within a liquid phase. This paper presents experimental works concerning semisolid metal processing of aluminium 7075 feedstock billets which were produced by direct thermal method. The flowability of feedstock billets was evaluated by an injection test processing unit. The feedstock billets were heated to a temperature of 620 °C by using a box furnace before transferred into a forming die. The formed feedstock billet was removed from the forming die after it was cooled to ambient temperature. Several analyses were conducted on the formed feedstock billets including dimensional measurement and microstructure analysis. The results show that the feedstock billets which contained the highest amount of free secondary phase were most successfully formed. Microstructure analysis results also revealed the formation of more globular and larger α–Al solid grains in the same feedstock billets. In this experimental work, the feedstock billets with higher amount of secondary (liquid) phase had a significant effect on formability. It is concluded that in order to achieve successful formability of the direct thermal method feedstock billets, the billets need to a have higher secondary phase content. Thus, important preparation methods of feedstock billets were characterised in order to allow for SSM processing.